A comprehensive review of bioactive peptides obtained from animal byproducts and their applications. Issue 10 (2nd October 2019) - Bechaux, Julia; Gatellier, Philippe; Le Page, Jean-François; Drillet, Yoan; Sante-Lhoutellier, Véronique
Abstract : Livestock generates high quantities of residues, which has become a major socioeconomic issue for the meat industry. Abstract : Livestock generates high quantities of residues, which has become a major socioeconomic issue for the meat industry. This review focuses on the identification of bioactive peptides (BPs) in animal byproducts and meat wastes. Firstly, the main bioactivities that peptides can have will be described and the methods for their evaluation will be discussed. Secondly, the various origins of these BPs will be studied. Then, the techniques and tools for the generation of BPs will be detailed in order to discuss, in the final part, how peptides could be used and assimilated. BPs possess diverse biological activities and can be strategic candidates for substituting synthetic molecules. In silico potentiality studies are a helpful tool to understand and predict BPs released from proteins and their potential activities. However, in vitro validation is often required. Although BP use is compelled by strict regulations in relation to the field of application, they are also limited by their low bioavailability and bioaccessibility. Therefore, it is important to test peptide stability during gastrointestinal digestion. Protective strategies have been discussed since their use could improve the stability and effectiveness of BPs.